Triply eclipsing triple stars in the northern TESS fields: TICs 193993801, 388459317, and 52041148. Issue 1 (1st December 2021) - Borkovits, T; Mitnyan, T; Rappaport, S A; Pribulla, T; Powell, B P; Kostov, V B; Bíró, I B; Csányi, I; Garai, Z; Gary, B L; Kaye, T G; Komžík, R; et al.
ABSTRACT: In this work we report the discovery and analysis of three new triply eclipsing triple star systems found with the TESS mission during its observations of the northern skies: TICs 193993801, 388459317, and 52041148. We utilized the TESS precision photometry of the binary eclipses and third-body eclipsing events, ground-based archival and follow-up photometric data, eclipse timing variations, archival spectral energy distributions, as well as theoretical evolution tracks in a joint photodynamical analysis to deduce the system masses and orbital parameters of both the inner and outer orbits. In one case (TIC 193993801) we also obtained radial velocity measurements of all three stars. This enabled us to 'calibrate' our analysis approach with and without 'truth' (i.e. RV) data. We find that the masses are good to 1–3 per cent accuracy with RV data and 3–10 per cent without the use of RV data. In all three systems we were able to find the outer orbital period before doing any detailed analysis by searching for a longer-term periodicity in the ASAS-SN archival photometry data – just a few thousand ASAS-SN points enabled us to find the outer periods of 49.28 d, 89.86 d, and 177.0 d, respectively. From our full photodynamical analysis we find that all three systems are coplanar to within 1°−3°. The outer eccentricities of the three systems are 0.003, 0.10, and 0.62, respectively (i.e. spanning a factor of 200). The masses of the three stars Aa, Ab, and B in the three systems are: 1.31, 1.19, 1.34, 1.82, 1.73, 2.19, and 1.62, 1.48, 2.74 M⊙, respectively.